Biomass carbon density in natural oak forests with different climate conditions and stand ages in northwest China. Issue 6 (2nd November 2018) - Yue, Jun-Wei; Guan, Jin-Hong; Yan, Mei-Jie; Zhang, Jian-Guo; Deng, Lei; Li, Guoqing; Du, Sheng
ABSTRACT: Oak forests are major communities in warm temperate forests in northern China. The dependence of biomass carbon accumulation and allocation patterns in above- and belowground on climate and stand age remains unclear. To quantitatively investigate the influence of temperature, precipitation, and stand age on the biomass carbon density (BCD) of each component in the forest and on the above/belowground allocation, field surveys were conducted at 32 plots with dimensions of 20 m × 50 m representing different ages and environmental conditions of natural oak secondary forests. Tree biomass was estimated using allometric biomass equations based on tree height and diameter at breast height (DBH). Biomass of shrubs, herbs, and litter was estimated by harvesting all the components. Carbon concentrations of all the plant components and litter were measured. Biomass carbon densities of trees and total ecosystems increased with increases in precipitation and stand age, but did not differ significantly with changes in air temperature. The ratio of above/belowground BCD showed significant positive correlation with stand age. Understory layers (shrubs and herbs) BCD showed positive relationships with precipitation, but had no obvious relations with stand age and temperature. BCD in litter layer decreased with increasing precipitation and had no definite variation trend along temperature and stand age gradients. The influence of precipitation on plant growth is greater than that of temperature in the forests. These findings indicate that water availability is the dominant environmental factor across these sub-humid climate sites.